NZVI©Au magnetic nanocomposite‐based electrochemical magnetoimmunosensing for ultrasensitive detection of troponin‐T cardiac biomarker. Issue 1 (25th September 2020) - Djebbi, Mohamed Amine; Boubakri, Saber; Braiek, Mohamed; Jaffrezic‐Renault, Nicole; Namour, Philippe; Amara, Abdesslem Ben Haj
Abstract: Early, inexpensive, reliable, and accurate diagnosis of cardiovascular abnormalities has become of crucial importance to prevent and halt their progression. Herein, we report a label‐free electrochemical magnetoimmunosensing for monitoring cardiac diseases through qualitative and quantitative detection of cardiac troponin‐T (Tpn‐T) in aqueous solution. In this context, a nanocomposite of gold nanoparticles coated a magnetic nanoscale zero‐valent iron core (NZVI©Au) is employed as a substrate to facilitate the electron transfer and to bind more primary Tpn‐T antibodies. The immunosensing platform consists of an anti‐cardiac troponin‐T antibody (Tpn‐T‐ab) modified NZVI©Au magnetic membrane attached onto a boron doped diamond (BDD) electrode. Sensing experiments were performed by the imposition of an external magnetic field at the backside of the electrode. The sensor response was performed using impedimetric assays, wherein the increase in the electron transfer resistance (Rct ) correlated with an increase in the concentration of Tpn‐T. Linearity was obtained in the range from 1 to 10 9 fg/mL with a detection limit of 0.354 fg/mL. The proposed platform exhibited high selectivity, high reproducibility, and good stability, while retaining more than 90% of the sensitivity after 2 weeks of storage at 4°C. The determination of Tpn‐T is well compared with previously reported methods and has been successfully tested in serum samples. This encouraging result suggests that the developed sensing strategy provides a high potential for the early assessment of Tpn‐T in point‐of‐care testing applications. Abstract : A new concept of label‐free impedimetric magnetoimmunosensor for Tpn‐T detection is described in this work. A nanocomposite of gold nanoparticles (AuNPs) decorating a magnetic NZVI core is synthesized and used as modifier of BDD electrode. The presence of the NZVI©Au core‐shell nanocomposite onto the BDD surface facilitated the covalent linking of primary Tpn‐T antibodies. The targeted Tpn‐T detection was then performed by means of electrochemical impedance measurements, wherein the increase in the electron transfer resistance (Rct) correlated with an increase in the concentration of Tpn‐T.